Push and Pull Factors in Women’s Rural Employment in India since Covid-19 - Bárcia de Mattos, Fernanda (2022)
The Covid-19 pandemic had a devastating impact on the world of work in India. It resulted in unprecedented job and income losses, reinforcing the adverse labour market situation of women. There was a significant contraction in demand as the crisis unfolded, and the effects of this contraction was exacerbated by an increase in the demand for unpaid care work as a result of business and school closures, and return migration. Return migration of working-age men pulledwomen out of employment, particularly in rural areas. Job and income losses and lower household income pushed women towards employment as a survival strategy to supplement family income, a strategy captured in the term “addedworker effect.” We postulate that the net result of these competing forces on women’s employment is ambiguous and investigate the pattern of rural women’s labour supply during the Covid-19 pandemic. The paper uses a mixed methods approach. Factors that played a determining role in changes to the labour force status of women-broadly classified through focus group discussions with women in selected rural areas-were further probed through econometric analysis. The main factors were loss of employment by members of the household, changes in household size during the period as migrants returned home, shifts in the time women spent on unpaid care work, and the number of young children in a household. The impact of these factors on entry into and exit from employment were estimated for both women and men in rural and urban India, using data from the Centre for Monitoring the Indian Economy (CMIE) Consumer Pyramids Household Survey (CPHS). The findings show complex coping strategies at the household level where women’s work–paid and unpaid–plays a critical role.